2003
DOI: 10.1509/jmkg.67.2.106.18604
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmentalism: Antecedents and Influence of Industry Type

Abstract: How does a business firm manage its relationship with the natural environment? What are the factors that influence the choice of such strategies? Does industry type matter? The authors introduce and operationalize the concept of corporate environmentalism in an effort to answer these questions. Using stakeholder theory, the authors identify four important antecedents to corporate environmentalism, namely, public concern, regulatory forces, competitive advantage, and top management commitment. The authors then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
964
6
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 861 publications
(1,032 citation statements)
references
References 52 publications
41
964
6
21
Order By: Relevance
“…• Differentiation-based competitive advantages (CAD): This variable included four items taken from Banerjee et al [27] and López-Gamero et al [79]. More specifically, in our study, we use loyalty of existing customers, attracting new customers, product image, and corporate image.…”
Section: Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…• Differentiation-based competitive advantages (CAD): This variable included four items taken from Banerjee et al [27] and López-Gamero et al [79]. More specifically, in our study, we use loyalty of existing customers, attracting new customers, product image, and corporate image.…”
Section: Competitive Advantagementioning
confidence: 99%
“…Many studies have already emphasized that environmental problems must be tackled from within the company as a whole [26]. On another level, Banerjee [27] highlighted the importance of functional strategies including Research & Development & Innovation (R&D&I). It is important to remember that managers face growing demand to develop not only new, environmentally-friendly products [28][29][30][31], but also new processes, which in recent decades have then been incorporated into the supply chain [32] with their subsequent effect on cost-based competitive advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these types of firms provide formal environmental training for their employees [21]. Recently established firms with a strong external environmental orientation pursue more proactive environmental strategies and integrate environmental issues at higher levels of strategy [42], and the founders of such firms are more concerned about how to satisfy the environmental demands of external stakeholders, e.g., consumers, supplier, alliance firms, government, and community [41].…”
Section: Firms' Environmental Orientationmentioning
confidence: 99%
“…Environmental orientation reflects the extent of companies in committing protection to the environment, which comes from their willingness to recognize and integrate environmental concerns into business strategy (Banerjee et al, 2003). Based on empirical research conducted by Banerjee (2002), it was reported that the environmental orientation may be focused internally or externally.…”
Section: Internal Environmental Orientationmentioning
confidence: 99%